Ard og åg i Nuristan - Edelberg, Lennart (Kuml, 1968)
Ard and Yoke in Nuristan In most parts of the world, one man ploughs with two draught animals. In Nuristan, two men plough with one ox [1]. The first description of this peculiar plough stems from Sir George Scott Robertson [2], who spent from September, 1890, till October, 1891, in the Bashgal valley, with a short trip to the Parun valley at the end of September and beginning of October, 1891 [2 a]. "Kámdesh village is between 6000 and 7000 feet above the sea-level. On April 4, 1891, ploughing began in that village ... "When the ploughing began the land was very soft from the lately melted snow. The ploughs used are so light that they can be easily carried over a woman’s shoulder. They are furnished with an iron tip, and have a prominent heel which stands high out of the shallow furrow [2 b]. They are of rough and primitive construction. Two women manage a plough, which is drawn by a small ox. The animal’s movements are controlled by one of the women placed on the off side, who grasps in her hands a long handle, fixed at the other extremity to the yoke, which works on the ox’s neck just in front of the hump. With the leverage afforded by this long handle the woman seems to have no difficulty in keeping the animal on a level course, or in turning him as she pleases. The plough itself is controlled by the second woman, who works alongside instead of behind the handle, which is fore and aft, and made to be grasped with both hands. After traversing the small field a few times, the women change places, so as to equalize the labour. Stooping over the handles sideways is more arduous than directing the course of the ox, although the woman staggering along and pushing against or dragging at the animal’s neck with the long yoke-pole appears to be doing more work. Musalmáns beyond the border always maintain that in Káfiristán a woman is harnessed to the plough with the ox, but this is not true. In the Kám tribe a man never touches the plough handle, but in other places men do work in the fields, even when they are not slaves. Musalmáns within the borders of this country, as at the little settlement near Gourdesh [3], plough in the usual way, one man doing all the work and driving a pair of oxen. At this place the two systems may be seen in operation in adjacent fields. No time is lost in getting the seed into the ground. On April 5, in a particular field near my house, the plough started breaking up the ground. On the following day the seed grain was being sown. After the plough had done its work, strings of women, in an irregular line, began breaking up the clods with hooked sticks or with implements like blunt axes, furnished with wooden handles and iron heads (cf. fig. 9). Another instrument looked like a light open crutch without the arm-rest, and was used upside down. One woman worked the single end, while a second, with ropes fastened to the forked extremities, dragged it up after each plunge into the broken-up furrow [4]. The sower casts handfulds of grain in what seemed a very niggardly fashion from a small goatskin bag carried in the left hand. On May 5, 1891, all the Kamdesh fields were ploughed, and in several places the crops were showing above the ground. The women were hard at work carrying manure." In the accompanying illustration, which is reproduced here (fig. 1) and merely bears the legend "Ploughing", two women are seen at work. One of them is on the unploughed side controlling the ox’s yoke bar, and the other is walking sideways in the newly ploughed soil, grasping the plough handle. The ox is of the zebu type with a prominent hump. We know that Robertson’s illustrations are drawn from photographs [5]. If the drawing is correct, the long yoke bar ends on the off side of the ox’s neck, where the yoke itself terminates, and both components seem to be fixed to a withy band round the neck. There is, though, reason not to rely too heavily on the drawing when it comes to detail, especially as Robertson’s use of the term "leverage" in this connection would otherwise be inappropriate. On the other hand, one has to admit that he writes of the handle being "fixed" to the yoke, as though handle and yoke were separate parts. I have only dwelt on this contradiction at all, because Robertson is usually so excellent and careful an observer. II On May 7th, 1948, Dr. Knud Paludan and I entered the Parun valley for the first time, from the long and narrow gorge-like Pech valley, which from the south leads up into the Hindu Kush at this point. I remember that he made the somewhat exaggerated exclamation, "Why, this is like a piece of Funen!" His remark should, however, be seen against the background of our having spent months in the ravines, and having now reached the glacier-formed valleys near the main watershed between those rivers that flow into the Indian Ocean and those that flow into the Caspian Sea. The valley bottom is here broken up into gently sloping fields, and on the pasturage between the fields, cows, sheep and goats were grazing. At that time I was not acquainted with Robertson’s description and wrote in my diary: "In the fields men are at work with a peculiar plough. One man walks at the side of the bull [5 a] and guides it with a long bar at right-angles to the direction of ploughing. He usually walks on the unploughed side, but rocks can make it most practicable for him to walk on the ploughed side every other furrow." On 29th May, when ploughing had finished, I acquired a plough of this type for the National Museum of Denmark (E 790 a-j). It comprises the following parts (fig. 2-3): a. Stilt and sole fashioned from one piece of hazel-wood [6]. This part of the ard is called in Paruni [7] žistapi (54) or kšo (48). The piece is perforated at three spots. Above is a smaller hole for the handle, in the middle a rectangular aperture for the beam and at the bottom of the actual sole a hole which continues forwards as a groove. In this hole the share is wedged with two wedges (k and 1). b. The handle (wrostating (54) or nekok (48)) is inserted into the stilt head, which is the result of an oblique incision on the left and right sides. The handle projects at variance with Robertson’s description- only slightly in front of the stilt. c. The beam (užpät (54) or pözdun (48)) is of poplar-wood. Its rear extremity is expanded sufficient to prevent it being drawn through the slot in the stilt. The beam can therefore only be introduced into the stilt from behind. E 790 has no wedge at this point, but on the photographs taken in 1948 and reproduced here, a wedge can be seen inserted in the rectangular hole in the stilt from in front. This wedge (waka (54)) was also observed in 1954. At its forward extremity, the beam is perforated by a little, horizontal hole, for the twisted withies which fasten the beam to the yoke. d-e. The share (weskašö (54) or ösköšö (48)) bears two letters, because I thought, prior to dismantling the plough, that it consisted of two parts. It is made of hazel-wood and is clearly worn. In the plough I examined in 1954, the share did not extend backwards beyond the sole. It is possible that the share is pushed further and further forwards in its slot as it becomes worn. In E 790 it is fixed by two wedges, the anterior above the share and the posterior below it. On the 1954 specimen there was only one wedge, placed as the anterior wedge in E 790. (Concerning these wedges, see below). f. Rope (iš (54) or viš (48)) of twisted withies. The rope is twisted so that the front end forms an eye, whereas the other end, where the twisted withies end, is knotted. This has to occur while the withies are still fresh. The rope is threaded through the little hole in the forward beam-end from the right, and the eye pushed through a corresponding hole in the yoke. The rope is duplicated as E 790 ff. g. Forked stick (kåndäik (48)), which is inserted in the eye of the rope where it projects in front of the yoke. The stick prevents the rope from slipping out of the hole in the yoke and the fork prevents the stick itself from falling out of the eye, if this should momentarily slip forwards during ploughing. h. The yoke (kōndūnd (54) or kundūn (48)) is of poplar-wood and measures 270 cm in length [8]. The part which lies against the hump is covered with woolly lamb skin [9], laced on with a thin strip of skin, and is perforated by two vertical holes for the yokepegs. On the off side of these is the horizontal rope-hole. Between this and the spherical grip at the other end of the yoke are a number of annular decorations. i and j. The yoke-pegs (konundugo (54) or lökduå (48)) [10] are bound together below by a white plied woollen cord (which was lost in transport). The pegs are round, slightly bent, about 48 cm long and expanded above so that they do not fall through the holes in the yoke. At the bottom of each peg, at the tie, a boss the size of a nut has been cut. k and I. Wedges (waka (54)) which hold the share. k is the superior, anterior and l the inferior, posterior wedge. l at least is of walnut-wood. The Parun plough (ebuik (48)) -and the Nuristani plough in general- is on account of its symmetrical construction clearly an ard. Since Robertson, however, has not used the term "ard", I prefer not to read more into the term "plough" than Robertson. In this article the word "ard" is therefore employed to denote ploughs without a coulter board, and "plough" includes the ard. It is worth noting that there is no iron whatsoever in the Parun ard. III I have seen the Nuristani ard at work in May, 1948, in Parun and in Kantiwo, in October, 1953, in Kamdesh, and again in Parun in the last days of May, 1954 [11]. In fig. 4, which like the following photographs relates to the valley floor below Pashki village, the ploughing of a field has just begun. There is no information as to whether the field has been sown, but it is probable. In the series of photographs fig. 4 to 8, both men are keeping mainly to the unploughed side. Ploughing has commenced at the edge of the field. The ploughman is apparently fully occupied in keeping the share in the soil (a stubble field, grazed by cattle) and keeping a straight furrow. Leading the ox at the yoke does not demand much effort. In the ard described above (E 790) the distance from the middle of the rope-hole in the yoke, to a point midway between the yoke-pegs where the hump touches the yoke, is about 21 cm. The distance from the rope-hole to the middle of the spherical grip which the man leading the ox grasps is, however, more than 10 times as long -224 cm. This means that the ox makes an effort 10 times that required of the man leading it. The weight of the yoke is also small, as it is made of poplar-wood. The fixing of the beam to the yoke with a rope and stick (which in this particular case is not forked) is clearly seen in fig. 6. The withy knot in the rope is away from the ox’s hide. In fig. 7, the ploughing has progressed so far, that only a small patch remains to be ploughed. In fig. 8, this patch has become so small, that the man who is controlling the ox must walk in the furrow. This is also a consequence of the fact that the plough is turning in the photograph. It can also be seen that the furrow avoids rocks in the field. Fig. 9 shows ploughing in another field. Maize has been sown on soil which has not been worked since harvest, and now grain is being ploughed in. While fig. 4-8 showed clockwise ploughing, fig. 9 shows anticlockwise ploughing, and the man controlling the yoke is therefore walking in the ploughed soil. The women kneeling in the foreground, who incidentally are all married [12], are breaking the clods with their wooden hoes [13]. This is in fact, a kind of harrowing after sowing. Their baskets are seen at the edge of the field. In the same photograph, it can be seen that the fields are slightly terraced and some of them gently sloping. I am not aware whether the field being ploughed can be irrigated, but ingenious irrigation channels of hollowed trunks direct small streams from the mountainside onto the fields at many places along the Parun valley. Since it is maize which has been sown, one would expect this field to be irrigable. To the right, winter goat-sheds can be glimpsed at the foot of the mountain below Pashki village. Fig. 10 looks down the valley to the point where it narrows and becomes V-shaped. A field is being ploughed which Iies next to the cemetery, which is seen on the left. This illustration has been included because the ard is apparently being drawn down the middle of a strip of ploughed soil. Perhaps this has to do with the fact that the yoke leader must have difficulty in moving between the graves, and seems unable to go further in than he is in the photograph. The furrows between him and the ox have presumably been ploughed with the ox moving in the opposite direction. The ploughed patch must then have been ploughed clockwise, but the last furrow has now been reached, namely the mid-furrow. I do not know how the remainder of the field was ploughed. Fig. 11 shows two women ploughing at Pronz. The winter goat-sheds east of the village can be seen in the background and the opening of the Pezgul valley behind them again. The photograph was taken around June 1st, 1954. At this late date, most of the men had gone into the mountain pastures with the flocks of cows, sheep and goats. The women seem to be at the completion of work on a little field which has probably been too near the goat-sheds for work on it to be profitable before. The fields are not enclosed in Parun. In fig. 12 we are further down the valley than the lowest village, Pashki. Here the valley sides are terraced to a greater extent, and the terraces are quite small, but not as small as in Wama [4]. The boy is ploughing and the girl leading. The photograph was taken at the beginning of June, 1954. I have also seen a grown man ploughing, helped by a woman, with the same distribution of work. I have also seen the Nuristani plough at work in Kantiwo, where the population belongs to another ethnic group (Siah Posh, dressed in black, in contrast to Parun valley’s Safed Posh, dressed in white). My diary of May 22nd, 1948 reads: "On to Kantiwo in the early morning after tea and maize bread. Kantiwo is situated on a rock in the middle of the valley, at the point where the Ptsigela valley joins from the north (see map, fig. 13). The valley has a quite different character to the Parun valley, although it is difficult to say where the difference Iies. Oaks (Quercus Balout) are more numerous, the flat valley-bottom not so wide. Many vertical peaks block the view to more distant snow-covered ones. North of Kantiwo on another hill is a castle-like building. Akbar -my Afghan assistant- is asking people where the malik is, and we are sitting on a stone waiting. A man seems to be ploughing his field for the second time with one ox and a plough of the same kind as the one in Pashki. Further on, a field is being ploughed with two teams of oxen -one drawing a plough of the same kind as in Pashki, the other with a plough of the type employed in Gusalak [14]". Finally, in October, 1953, we met the single-drawn plough in Kamdesh. The situation has been filmed [15]. A maize-stub field had been sown with wheat. Robertson is correct in stating that the grain was sown in what seemed a very niggardly fashion with handfuls of grain from a small (hairy) goatskin bag. Two men [16] ploughed back and forth, the yoke-leader alternately walking on the ploughed and the unploughed earth. The plough was of a slightly different construction to the Parun plough and with an iron share. Kamdesh is situated in an area with deeply cut V-valleys, but at the site of the village itself, the terrain is for some reason more rounded, and it is here that the plough can be used. I have also heard that the Nuristani ard can be found higher up the Bashgal valley, where the terrain is reputed to resemble that of the Parun valley (see ard distribution, fig. 14). IV The most characteristic feature of the Nuristani ard, as we know it from Parun in particular, is surely the manner in which the beam is entered from behind into the stilt-sole, which is in one piece. I have met with the same construction on my journey to Badaksham and Minjan [16 a]. In Badakshan the plough is very stoutly constructed, in Minjan it is light and with a wooden share as in Nuristan. These observations date from July, 1948. In both localities, a team of oxen is used to draw the plough. There is a lively traffic of people from Minjan to Parun via the 4,600 meter high Weran pass (= Kamah pass). They carry rock salt and now and again opium. So it is hardly surprising that the same ard construction is found in both places. All things being considered, as I also emphasized in the first lines of this article, it is the use of a single ox as a draught animal which makes the Nuristani ard peculiar, but not unique. P. V. Glob gives examples of both a single horse (the rock engraving at Tegneby in Bohuslän) and single oxen having been used-in historical times moreover in Saxony and Ireland right up till 1845. In all these instances the plough is fastened to the draught animal’s tail [17]. This leaves the question of whether the long steering yoke is peculiar to Nuristan [18]. V Scandinavia is one of the richest areas for finds of prehistoric ploughs. All the Nordic ploughs have been found in bogs. If a yoke like the Nuristani one occurred in prehistoric Europe, the bogs are surely the only possible natural repositaries. But a yoke of this kind can in peat digging easily be mistaken for the young stem of a fallen tree or rather perhaps, as it is without bark, for the mast of a boat. Holes for yoke-pegs and rope would, however, decide the issue. Rock engravings constitute important material in plough research. Engravings are known where ox and plough are shown in one piece, and P. V. Glob has with good reason interpreted these engravings as a sign that the plough was fastened to the ox’s tail an arrangement which has notoriously occurred [17], although one would expect the tail vertebrae to be displaced. If one were to imagine a rock engraving of the Nuristani plough, it would presumably also show the ox and plough in one piece. However, one would stipulate a human figure beside the ox’s head, steering the plough with an extended yoke. An engraving of this kind is as far as I know unknown. It would possibly look like the vignette on p. 150. Lennart Edelberg